2014
DOI: 10.1111/add.12619
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal associations between cigarette consumption and DSM-IV nicotine dependence criteria in adolescent smokers

Abstract: Aims To examine the interrelationships between cigarette consumption and DSM-IV nicotine dependence (ND) criteria from smoking onset in adolescence up to seven years later, adjusting for alcohol consumption and DSM-IV alcohol dependence (AD) criteria. Design A cohort drawn from grades 6-10 in an urban school system was interviewed five times at 6-month intervals (Waves 1-5) and 4.5 years later (Wave 6). A parent was interviewed three times. Setting Chicago, Illinois. Participants Recent smokers (n=409). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…Once regular smoking patterns are established, however, prior smoking behavior becomes such a strong predictor of future smoking behavior (Selya, Dierker, Rose, Hedeker, & Mermelstein, 2012; Selya et al, 2013) that nicotine dependence becomes a weak or insignificant predictor. Early-emerging nicotine dependence assessed from novice smokers, then, may provide a special insight into one's initial sensitivity or susceptibility to nicotine dependence, while nicotine dependence assessed from more experienced smokers is likely to be conflated with the subsequent effects of smoking on nicotine dependence (Hu, Griesler, Wall, & Kandel, 2014). Put another way, nicotine dependence and smoking have a bi-directional relationship (Doubeni, Reed, & Difranza, 2010), and early-emerging nicotine dependence assessed from novices may more precisely measure one's susceptibility to future chronic smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once regular smoking patterns are established, however, prior smoking behavior becomes such a strong predictor of future smoking behavior (Selya, Dierker, Rose, Hedeker, & Mermelstein, 2012; Selya et al, 2013) that nicotine dependence becomes a weak or insignificant predictor. Early-emerging nicotine dependence assessed from novice smokers, then, may provide a special insight into one's initial sensitivity or susceptibility to nicotine dependence, while nicotine dependence assessed from more experienced smokers is likely to be conflated with the subsequent effects of smoking on nicotine dependence (Hu, Griesler, Wall, & Kandel, 2014). Put another way, nicotine dependence and smoking have a bi-directional relationship (Doubeni, Reed, & Difranza, 2010), and early-emerging nicotine dependence assessed from novices may more precisely measure one's susceptibility to future chronic smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the cross-sectional association between nicotine dependence and smoking frequency increases in strength over time (Selya, Dierker, Rose, Hedeker, Tan, et al, 2012), and that nicotine dependence and smoking behavior have strong reciprocal relationships based on cross-lagged analyses (Doubeni et al, 2010), with smoking behavior being a stronger predictor of nicotine dependence symptoms than vice versa (Hu et al, 2014). The current study is consistent with this literature in that it shows the importance of early-emerging nicotine dependence in establishing regular and long-term smoking patterns, and extends it by showing that ND assessed within 2 years of age 15 predicts smoking frequency beyond age 24, over and above concurrent past-week smoking frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The marginal probability distribution of the condition showed the success rate was 63.64%. The low PYS indicated the weak nicotine addiction (Heatherton, Kozlowski, Frecker, & Fagerstrom, 1991;Hu, Griesler, Wall, & Kandel, 2014). The high SA implied that these people had some health problems (DeJean et al, 2013;Zung, 1971) so that they had to keep smoking abstinence because the doctors usually advised them doing it when they go to see doctors.…”
Section: Discussionmentioning
confidence: 99%
“…[17, 28, 37, 49] The prevalence of craving and other symptoms increases to about 95 % among youth who have smoked 100 or more cigarettes [17, 52, 53]. …”
Section: Main Textmentioning
confidence: 99%
“…Early symptoms of dependence predict continued and escalating smoking [37]. Shortening latencies promote an escalation in smoking frequency, while more frequent smoking promotes the progression of dependence in a mutually reinforcing cycle [45, 53, 55]. The number and intensity of the symptoms experienced by very light smokers is disproportionate to their tobacco consumption, with some nondaily smokers describing their withdrawal symptoms as unbearable [5658].…”
Section: Main Textmentioning
confidence: 99%